Structural Design of a 2,000 DWT Tanker Jetty with Deck-on-Pile System at Kabil, Batam Island - Panusunan Panusunan; Sumitro D.P Simanungkalit; Januarto Januarto; Herlina Suciati (Studi Akuntansi dan Bisnis Indonesia, 2025)
Purpose: This study designs a 2,000 DWT tanker jetty at Kabil, Batam Island to support offshore marine loading operations. Methodology: The study uses site investigation data (topography, soil, tides, waves) and secondary data from BMKG and related authorities. Structural design and analysis were conducted using ETABS based on Indonesian standards SNI 2847:2013 and SNI 03-1726-2002. Results: The jetty adopts a deck-on-pile system with an elevation of +5.29 m. Structural elements, including beams, slabs, dolphins, and Ø600 mm steel piles (capacity 187.17 tons), satisfy design loads with adequate safety factors. Fender and mooring systems are designed for a 2,000 DWT vessel. Conclusions: The structure meets strength and serviceability requirements under all load combinations, ensuring safe and efficient operations. Limitations: The study excludes cost analysis, construction sequencing, environmental assessment, and dynamic seismic analysis. Contribution: This research provides a complete structural design framework for deck-on-pile jetty systems in shallow offshore environments applicable to similar port infrastructure in Indonesia.